(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This research paper aims to explore and analyze the challenges encountered by disabled children in primary schools, focusing on the perspectives of parents and teachers. The study gathered data from 100 parents and teachers through surveys and interviews to identify the key problems faced by disabled children and understand the perceptions of those involved in their education. The study revealed that many disabled boys enjoyed their studies and had positive relationships with teachers and peers, while disabled girls reported fewer conflicts. Both disabled boys and girls aspired to become doctors. Teachers, whether specially trained or not, invested extra effort in teaching disabled students. Opinions varied on whether disabled students could achieve the same success as their peers, and there were differing views on school benefits and special education. Parents’ income influenced their perceptions of the impact of disability on their own well-being and their child’s abilities. Transportation and care arrangements differed between income groups, but most parents noted a generally normal attitude from other children towards their disabled child. The findings reveal several common obstacles, including inadequate resources, lack of inclusive teaching methods, social isolation, and insufficient training for teachers. By understanding these challenges, educators, policymakers, and parents can collaborate to create a more inclusive and supportive learning environment for disabled children in primary schools.